Rechargeable Magnesium Batteries using Conversion‐Type Cathodes: A Perspective and Minireview. Issue 10 (3rd July 2018) - Zhang, Zhonghua; Dong, Shamu; Cui, Zili; Du, Aobing; Li, Guicun; Cui, Guanglei
Abstract: Rechargeable magnesium (Mg) batteries are one of the potential contenders to replace current Li‐ion batteries to power future electric vehicles with lower cost, higher safety, and extended mileage. To achieve this goal, both high‐voltage intercalation‐type cathodes and high‐capacity conversion‐type cathodes are considered. However, there are still no reports to compare rechargeable Mg batteries with the state‐of‐the art Li‐ion batteries in terms of their overall performance. Also, potential cathode materials to deliver higher energy density in rechargeable Mg batteries are rarely summarized. Here, the practically accessible energy characteristics of Mg‐based and Li‐ion chemistry are presented and compared using practical cell‐level modeling. Among the reported cathode materials, only sulfur, a typical conversion‐type cathode, is capable of delivering a higher energy density than current lithium‐ion batteries in terms of energy density. Since the electrochemical performance of the conversion‐type cathode is determined by the electrolyte at the current stage, the recent developments of Mg‐ion electrolytes, particularly those with non‐nucleophilic features, are reviewed. The recent advances are then summarized and the future challenges of high‐capacity conversion‐type cathodes for rechargeable Mg batteries are analyzed. The proposed guidelines provide new insights for developing high‐energy‐density Mg batteries. Abstract : Practically accessible volumetric and gravimetric energy densities are evaluated for rechargeable Mg batteries, which highlight the greater promise of high‐capacity conversion‐type cathodes than high‐voltage intercalation‐type cathodes in competing with mature lithium‐ion batteries. Recent progress and common challenges of the non‐nucleophilic electrolytes and sulfur cathodes are reviewed, providing fundamental insights for developing future high‐energy‐density rechargeable Mg batteries.